Nour Travel & Tours - Mohd Rosli, Ayu Natasha Emylin; Pazil, Farhanim; Hairurozy, Nur Fatnun Nafiah; Aaftab Alam, Puteri Nur Ainuldina; Mohammad, Sa’idah Solehah; Zakaria, Siti Rabiatul Adawiyah; Juhari, Joeaiza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The essence of entrepreneurship is the ability to recognize and address gaps in the market. Nour Travel & Tours' creative approach to Hajj pilgrimage services is an ideal representation of this approach. An overview of our company's dedication to inclusivity is provided, which also describes how we serve a broad range of customers, including the elderly and those with disabilities. Our services are intended to ensure that everyone who believes in the divine, regardless of physical limitations, can participate in the Hajj, one of the most important religious pilgrimages for Muslims. We discuss the operational tactics that allow us to offer customized travel options, such as on-site assistance and specialist lodging, guaranteeing a respectable and rewarding pilgrimage experience. In addition to being in line with the fundamentals of entrepreneurship, our business plan shows how the travel sector can have a positive social impact. This summary showcases our efforts to enhance the Hajj experience, demonstrating our commitment to entrepreneurial excellence and developing a more inclusive pilgrimage landscape.